The Role of Non-Governmental Organizations (NGOs) in Supporting the Implementation of the Bone Regency Government's Work Program - Heri Afian; Erviandi Erviandi; Mustigawati Mustigawati; Muh Sawir; Syarifuddin Yusmar (Public Resource Innovation Management and Excellence, 2025)
This study aims to critically analyze the role of Non-Governmental Organizations (NGOs) in supporting the implementation of the Bone Regency Government's work programs. The study focuses on two main issues: the positive contribution of NGOs in strengthening regional development through partnerships with the government, and the identification of inhibiting factors resulting from the misalignment of interests between the two actors. The research method used is a qualitative case study strategy, through in-depth interviews, participant observation, and official document review. The results show that NGOs in Bone Regency have a dual role: on the one hand, strengthening development governance through community participation, community empowerment, and social advocacy; but on the other hand, presenting potential obstacles in the form of weak accountability, limited organizational capacity, and friction with the government due to differences in program orientation. The government-NGO relationship in Bone is thus ambivalent, namely collaborative and confrontational. This study emphasizes that the role of NGOs cannot be viewed merely as passive partners, but rather as actors with significant social, political, and economic bargaining power. These findings are expected to provide theoretical contributions to the study of collaborative governance at the local level, as well as practical recommendations for local governments and NGOs in building more adaptive, transparent, and sustainable partnerships.